ASSESSMENT OF ECOTOURISM AT TENGANAN PEGRINGSINGAN, BALI WITH THE INDONESIA SUSTAINABLE TOURISM AWARD (ISTA) - Ester Yuan Rahayu (Jurnal Ilmiah Hospitality, 2019)
Assessment is needed to measure ecotourism outcomes and impacts. Assessment indicators can be used to manage and guide the practice and development of tourism destinations. Indonesia has an assessment standard developed to evaluate sustainable tourism practices, namely the indonesia sustainable tourism award (ista). Ista is aligned with and officially recognized by the gstc. This research investigates the ease and effectiveness of implementing ista standards in the context of a community-based ecotourism destination. The research was conducted in tenganan pegringsingan village through direct observation, questionnaires and interviews with the local community and jed (jaringan ekowisata desa) managers. The results demonstrate that ista was a useful assessment tool for a mature ecotourism destination which was established on the basis of local culture and wisdom. It was also found that a number of criteria were difficult to understand and apply in self assessment of compliance and some modification of the standard may be necessary. The results of this research were applied to create recommendations for ecotourism management and to give feedback on the implementation of ista in indonesia.